2006
DOI: 10.1182/blood-2006-04-016444
|View full text |Cite
|
Sign up to set email alerts
|

Kinin receptor expression during Staphylococcus aureus infection

Abstract: An inappropriate host response to invading bacteria is a critical parameter that often aggravates the outcome of an infection. Staphylococcus aureus is a major human Gram-positive pathogen that causes a wide array of community-and hospital-acquired diseases ranging from superficial skin infections to severe conditions such as staphylococcal toxic shock. Here we find that S aureus induces inflammatory reactions by modulating the expression and response of the B1 and B2 receptors, respectively. This process is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 46 publications
0
25
0
1
Order By: Relevance
“…This mechanism could explain the in vivo contact activation and bradykinin liberation seen during streptococcal invasive infections (2,11,33,38). Local and controlled activation of the contact system has been discussed to promote bacterial invasive spread via bradykinin-induced vascular leakage, since inflowing nutrient-rich plasma to the infected tissue site might serve as a route for the disseminating pathogen (6,22,36,39). On the other hand, the systemic activation of the contact cascade is supposed to contribute to the pathophysiology of severe invasive infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This mechanism could explain the in vivo contact activation and bradykinin liberation seen during streptococcal invasive infections (2,11,33,38). Local and controlled activation of the contact system has been discussed to promote bacterial invasive spread via bradykinin-induced vascular leakage, since inflowing nutrient-rich plasma to the infected tissue site might serve as a route for the disseminating pathogen (6,22,36,39). On the other hand, the systemic activation of the contact cascade is supposed to contribute to the pathophysiology of severe invasive infections.…”
Section: Discussionmentioning
confidence: 99%
“…Many invasive pathogens exploit plasmin as a virulence factor to degrade fibrin clots, overcome tissue barriers, and evade peptide-derived host immune defenses (34,35). Under normal conditions, soluble plasmin is immediately inhibited by ␣2-antiplasmin (6,22,32,36); however, the SK-plasmin complex is protected from this inhibitor and promotes uncontrolled plasmin activity. We found that the degradation of HK by SK generates high levels of bradykinin and can be induced independently of PK.…”
Section: Discussionmentioning
confidence: 99%
“…B1R은 주 로 급성 통증 유발과 관련이 있으며, B1R-리간드 반응에 의해 CXCL5와 같은 케모카인의 발현을 유도하여 neutrophil을 감염 부위로 침윤시킬 수 있다 (Duchene et al, 2007). Bradykinin 2 Receptor (B2R)는 여러 조직에 널리 분포하고 있으며, 활성화되 면 혈관 팽창을 통해 염증반응을 돕는 것으로 알려져 있다 (Hall, 1997 (Bengtson et al, 2006;Kaman et al, 2009;Ha, 2011a, 2011b 져 있다 (Kolli et al, 2008). 본 연구에서는, 녹농균에 의한 BR 발현 증가에 Ndk가 관여하며, 이러한 효과는 주요 PAMP로 알 려진 flagella가 함께 필요함을 규명하였다.…”
unclassified
“…Previously, we reported that expression of the bradykinin receptor (BR) is induced in response to et al, 2006;Kaman et al, 2009; Ha, 2011a, 2011b …”
mentioning
confidence: 99%
“…Additionally, a microbial proteinase-independent activation of the host plasma kininforming system was recently suggested to proceed after adsorption of its proteinaceous components on Candida spp. cell walls Karkowska-Kuleta et al, 2010), a mechanism also extensively characterized for numerous bacterial pathogens (Ben Nasr et al, 1995Mattsson et al, 2001;Bengtson et al, 2006). However, a direct kininogenase activity of candidial proteinases has not yet been described.…”
Section: Introductionmentioning
confidence: 99%